2022
DOI: 10.3390/ijerph192215370
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Misinformation, Self-Perceived Risk and Fear, and Preventive Measures Related to COVID-19 in Spanish University Students

Abstract: The “infodemic” is one of the main obstacles in the fight against the COVID-19 pandemic. In order to face it, health literacy (HL) is essential since it allows for knowledge about COVID-19 and the practice of preventive measures to be fostered. This is especially relevant in university students due to their idiosyncrasy. This study aims to evaluate the level of HL related to COVID-19 (HLC), risk perception, misinformation, and the attitudes and behaviors adopted to prevent the spread of coronavirus in Spanish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…It is probable that three years after the onset of the pandemic, exhausted nurses are more afraid than they were pre-pandemic of getting an influenza infection in the coming winter season. Yet, several studies suggest that COVID-19 fear is positively associated with acceptance of and adherence to preventive measures among healthcare workers and the general public [ 51 , 52 , 53 ]. It seems to be that the higher the perceived susceptibility, the more precautions are taken by the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that three years after the onset of the pandemic, exhausted nurses are more afraid than they were pre-pandemic of getting an influenza infection in the coming winter season. Yet, several studies suggest that COVID-19 fear is positively associated with acceptance of and adherence to preventive measures among healthcare workers and the general public [ 51 , 52 , 53 ]. It seems to be that the higher the perceived susceptibility, the more precautions are taken by the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Socialization is one of the characteristics (developmental stage, invulnerability, lack of risk perception, etc.) that predispose young adults to risky behaviors (Bas-Sarmiento et al, 2022). Moreover, in the Spanish culture, there is a social dimension in the co-use of tobacco, alcohol, and coffee consumption (Vinader-Caerols et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…6 It is hypothesized that HISB may have a positive influence on patient health advocacy and treatment adherence, though many have cited concerns surrounding the opportunities for medical misinformation. [7][8][9] A survey study by Neely et al 10 found that 63% of social media users from a sample of 1003 United States (US) based adults were unlikely to fact-check health-related media with a medical professional, despite 76% of participants confirming "a little" reliance on social media. Medical misinformation is defined as any claim of health-related fact that does not align with the evidence-based scientific consensus.…”
Section: Background and Contextmentioning
confidence: 99%